Recombinant BCG expressing LTAK63 adjuvant induces superior protection against Mycobacterium tuberculosis - MILLS, KINGSTON (My University, 2017)
In order to develop an improved BCG vaccine against tuberculosis we have taken advantage of the adjuvant properties of a non-toxic derivative of Escherichia coli heat labile enterotoxin (LT), LTAK63. We have constructed rBCG strains expressing LTAK63 at different expression levels. Mice immunized with BCG expressing low levels of LTAK63 (rBCG-LTAK63lo) showed higher Th1 cytokines and IL-17 in the lungs, and when challenged intratracheally with Mycobacterium tuberculosis displayed a 2.0-3.0 log reduction in CFU as compared to wild type BCG. Histopathological analysis of lung tissues from protected mice revealed a reduced inflammatory response. Immunization with rBCG-LTAK63lo also protected against a 100-fold higher challenge dose. Mice immunized with rBCG-LTAK63lo produced an increase in TGF-β as compared with BCG after challenge, with a corresponding reduction in Th1 and Th17 cytokines, as determined by Real Time RT-PCR. Furthermore, rBCG-LTAK63lo also displays protection against challenge with a highly virulent Beijing isolate. Our findings suggest that BCG with low-level expression of the LTAK63 adjuvant induces a stronger immune response in the lungs conferring higher levels of protection, and a novel mechanism subsequently triggers a regulatory immune response, which then limits the pathology. The rBCG-LTAK63lo strain can be the basis of an improved vaccine against tuberculosis.
PUBLISHED
Keywords: BCG vaccine; BCG vaccine